Biomarkers in drug development: potential use and challenges - Halim, Abdel-Bassett (Henry Stewart Talks, 2013)
Biomarkers in drug development, Classes of biomarkers, Crisis in pharmaceutical development, Potential value of biomarkers and personalized medicine to enhance probability of success, Challenges (biology, pre-analytical, analytical), Possible mitigation
Reviewed at 2022/02/24